THE PREDICTION OF ATRIAL FIBRILLATION RECURRENCE AT VARIOUS METHODS OF SINUS RHYTHM RECOVERY - T. Y. Gromyko; S. A. Sayganov (Рациональная фармакотерапия в кардиологии)
Aim. To estimate probability of atrial fibrillation (AF) recurrence at various methods of sinus rhythm recovery. Material and methods. Patients (n=153) with nonvalvular AF lasting from 24 hours to 6 months were examined. All patients were divided into 3 groups. In group 1 (n=49) sinus rhythm was restored by the drug therapy, in the group 2 (n=57) – by the electrical cardioversion, and in the group 3 (n=47) patients underwent radio-frequency isolation of pulmonary veins. Echocardiography was performed in all patients during AF, and also on the 1, 3, 5, 15 days and in 6 months after sinus rhythm recovery. Results. The absence of AF paroxysms within first 2 weeks after sinus rhythm recovery was a significant predictor of sinus rhythm preservation (р<0.001) and reduction in a number of AF paroxysms р<0.001 during 6 months of follow-up. Emergence of AF paroxysms during the first 2 weeks predicted an increase of their probability within next 6 months (odds ratio=15.37). Significant interrelation between the time of left atrium function restoration (peak A<0.5m/s) and probability of AF paroxysms emergence in early (up to 2 weeks) and late (till 6 months) follow-up periods was also observed (р<0.05). Conclusions. Peak A>0.5 m/s measured by transmitral flow in the first 24 hours after sinus rhythm recovery as well as absence of AF paroxysms within 2 first weeks after sinus rhythm recovery were significant predictors of the sinus rhythm preservation up to 6 months at any type of cardioversion.